Penerapan Model Project Based Learning untuk Meningkat Hasil Belajar Pendidikan Pancasila Siswa Sekolah Dasar - Qisthi Mawardah; Akhwani Akhwani; Sianah Sianah (STKIP AL HIKMAH SURABAYA, 2022)
The aim of the research using this method is to improve and improve student learning outcomes through the application of the Project Based Learning (PjBL) learning model in class 1 Pancasila Education subjects. This research uses classroom action research (PTK), where this research method provides direct action in in class. Based on the results of research and discussions regarding improving student learning outcomes using the Project Based Learning (PjBL) learning model, it can be concluded that the Project Based Learning (PjBL) learning model can improve Pancasila Education learning outcomes for class 1 students at SDN Jemur Wonosari I/417 Surabaya. This is proven from the data that has been obtained, namely in cycle I as many as 16 students completed their learning with a score of 57%. Meanwhile, there were 12 students who did not complete with a score of 43%. Meanwhile, in cycle II, 22 students completed their studies with a score of 78%. Meanwhile, there were 6 students who did not complete with a score of 22%.